Connectives in Igbo: A syntactic analysis of connectives in the Standard Igbo and the Nsukka dialect - Ifyede, Henrietta Chimto (University of Cape Town, 2020)
This study provides a description of connectives in Igbo, focusing on the Standard Igbo and Nsukka dialect varieties. These connectives in Igbo are realised mainly through conjunctions and a few adverbials and previous works on connectives in Igbo have hugely focused on connectives in the Standard Igbo variety (Emenanjo 2015). And so, the main aim of this work was to identify the connectives in both varieties and conduct a syntactic comparative analysis, thereby adding to the existing connectives in the literature. This work explores connectives in the Standard Igbo and the Nsukka Dialect and their similarities. It also highlights the difference between connectives in both varieties. Data for this work was gotten through the researcher's intuitive knowledge and by conducting unstructured interviews with native speakers. The major finding is that there are a limited number of connectives in the Standard Igbo and even a fewer number in the Nsukka Dialect and these connectives are more similar than different syntactically. One of the questions addressed by the study is the role of English in the Igbo language in general, and how this specifically affects connectives in Igbo. It does so by thoroughly reviewing code-switching and related concepts. This work concludes that the differences in connectives in both varieties are merely morphological.